Variação sazonal da composição, densidade e biomassa da comunidade fitoplanctônica do Rio São João, Parque Nacional do Iguaçu, Paraná, Brasil - Bortolini, Jascieli Carla (2010)
This study aimed to analyze the seasonal variation of the phytoplankton community structure in a subtropical river through composition, richness, density and biomass data in function of environmental variables. Samplings of phytoplankton and abiotic variables were carried out between August 2008 and July 2009, at three stations in longitudinal section, at the subsurface of São João River, tributary of the Iguaçu River, Paraná State, Brazil. To estimate the density we used the Utermöhl method and biomass estimation was performed using the biovolume. Abiotic variables were summarized by Principal Component Analysis (PCA) and the data density and biovolume of species by Detrended Correspondence Analysis (DCA). We identified 221 Bacillariophyceae taxa, the more representative group. The most species-rich taxa reached 40 in September 2008 at station 1. The highest values of phytoplanktonic densities were recorded on March 2009, station 1. The Chrysophyceae and Baccillariophyceae classes were dominant in density. The biovolume was generally low, not exceeding one 1 mm3.L-1 with the highest value recorded in March 2009, station 2. The seasonal variation in phytoplankton composition were due to alternation of limnological conditions, especially in relation to temperature, which caused the change in structuring phytoplankton, however, the spatial composition was very similar, due to the proximity of the stations, and also the similarity of the distribution of the community in lotic environments, due to the unidirectional flow.